THE LEGAL BASIS OF THE DECREES OF THE COUNCIL OF PEOPLE’S COMMISSARS OF THE RSFSR АBOUT ARCHIVE AFFAIRS AND ARCHIVAL IDEOLOGIES IN KAZAKHSTAN - Hassanaeva, Leila; Altymyshova, Zuhra (Journal of history, 2017)
The article examines the problems of the establishment of archival business in Kazakhstan and the peculiarities of the holding by the Soviet authorities of archival policy. Attention has also been paid to the organization of provincial and district archives in Kazakhstan and analysis of policy documents on historical, cultural and legal norms of archival activities. In the article the author analyzes the work of the archives of the district of Kazakhstan. The author on the basis of archival sources characterizes the success of archival construction, as evidenced by the fact that in 1925 the Unified State Archive Fund of the RSFSR was organized and all materials were divided according to the tome of their appearance on the pre-revolutionary and post-revolutionary respectively formed the Historical Archive and archive of the October Revolution.